The Effectiveness of Project-based Multi-representation Discourse on Junior High School Students’ Science Process Skills - Safitri, Mutiara; Susongko, Purwo; Hayati, Muriani Nur (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2020)
The purpose of this study was to determine the effectiveness of the implementation of Project-based Multi-Representation Discourse model in improving students’ science process skills. The method used was the quasi-experiment with pretest-posttest control group research design. The population in this study was VII graders of SMP N 17 Tegal. The sample was selected using the cluster random sampling techniques. The data were taken through tests, questionnaires, and documentation. The results showed that the students learning using the Project-based Multi-Representation Discourselearning model had an average N-gain percentage of 72.27%. The percentage score was higher than the students studying using the Multi-Representation Discourse (MRD) learning model which had an average N-gain percentage of 42.50%. The results of the data analysis showed that the Project-based Multi-Representation Discourselearning model is effective enough to be applied and has an effect on improving science process skills.